The impact of the motivation on the employee's performance: an Islamic perspective / Najmuddin Erbakan Abdul Shukor - Abdul Shukor, Najmuddin Erbakan (2016)
This paper's main objective is to identify the main factor that influence employee performance. The variables considered are monetary incentive, job security, promotion opportunity and Islamic perspective. The sample of this study comprises of 50 respondent and 50 questionnaire each of dependent and independent variables on a monthly basis over 5 month period from February 2016 until June 2016.